Improved xylitol production by expressing a novel d-arabitol dehydrogenase from isolated Gluconobacter sp. JX-05 and co-biotransformation of whole cells. (July 2017) - Qi, Xianghui; Zhang, Huanhuan; Magocha, Tinashe Archbold; An, Yingfeng; Yun, Junhua; Yang, Miaomiao; Xue, Yanbo; Liang, Shuhua; Sun, Wenjing; Cao, Zheng
Graphical abstract: Highlights: An ardh gene from a new isolated Gluconobacter sp. JX-05 was expressed and analyzed. A novel NAD-dependentd -arabitol dehydrogenase was characterized and modeled. The NAD-dependent ArDH was firstly used in the co-biotransformation ofd -arabitol. The xylitol production was improved by the whole cell microbial co-biotransformation. Abstract: In the present study, a novel ardh gene encodingd -arabitol dehydrogenase (ArDH) was cloned and expressed in Escherichia coli from a new isolated strain of Gluconobacter sp. JX-05. Sequence analysis revealed that ArDH containing a NAD(P)-binding motif and a classical active site motif belongs to the short-chain dehydrogenase family. Subsequently, the optimal pH and temperature, specific activities and kinetic parameter of ArDH were determined. In the co-biotransformation by the whole cells of BL21- ardh and BL21- xdh, 26.1 g/L xylitol was produced from 30 g/Ld -arabitol in 22 h with a yield of 0.87 g/g. The xylitol production was increased by more than two times as compared with that of Gluconobacter sp. alone, and was improved 10.1% than that of Gluconobacter sp. mixed with BL21- xdh .